Climate change‐triggered land degradation and planetary health: A review. (24th August 2021) - Talukder, Byomkesh; Ganguli, Nilanjana; Matthew, Richard; vanLoon, Gary W.; Hipel, Keith W.; Orbinski, James
Abstract: Land is a vital natural resource for human socio‐ecological wellbeing. Around the world, land is being degraded due to various natural and anthropogenic factors such as flooding, wind erosion, agriculture and human settlement, and anthropogenic climate change. While significant research has been conducted on the separate dyads of: (1) anthropogenic climate change and land degradation and (2) land degradation and health, limited consideration has been given to the cause‐and‐effect relationships between anthropogenic climate change‐triggered land degradation and planetary health consequences. Using a systematic literature review and the driving force, pressure, state, exposure, effect (DPSEE) framework, this study synthesizes the complex causal relationships of anthropogenic climate change‐triggered land degradation and its planetary health consequences. Our findings demonstrate that anthropogenic climate change has induced and accelerated natural and anthropogenic land degradation through an array of pathways, resulting in planetary health consequences that can be grouped into six categories: (1) food and nutritional insecurity, (2) communicable and noncommunicable diseases, (3) livelihood insecurity, (4) physical and mental health, (5) health hazards related to extreme weather events, and (6) migration and conflict. Interlinkages exist between these six planetary health impact categories, adding to the complexity of the causal pathways. These collective impacts are hampering the realization of the UN Sustainable Development Goals around the world. The findings of this study and our DPSEE framework can help policymakers identify and integrate actions to better manage the planetary health impacts of climate change‐induced land degradation.